Reflexões sobre os impactos dos agrotóxicos na saúde dos ecossistemas: os nanoagrotóxicos - Aline Espíndola; Antonio Azeredo; Armando Meyer; Josino Costa Moreira (Vigilância Sanitária em Debate, 2026)
Introduction: The advantages associated with the use of nanotechnology have led to numerous applications across a wide range of fields. Mastering the ability to manipulate the unique properties of nanomaterials tailoring them to human needs has been pivotal in this regard. In agriculture, the use of formulations containing nanoparticles with agrochemical activity (such as nano-pesticides and nano-fertilizers) is believed to offer the potential for increased productivity, reduced costs, and a decrease in adverse impacts on ecosystem health. Key among these benefits is greater profitability resulting from reduced losses and enhanced pest control effectiveness. However, the widespread adoption of this technology has been constrained by a lack of knowledge regarding its impact on ecosystem health stemming from the variability of formulations and the physicochemical characteristics of nanoparticles at their sites of action as well as the absence of an internationally harmonized risk assessment methodology that accounts for current uncertainties. Conclusions: Existing uncertainties must be resolved before governments authorize the large-scale registration and use of such formulations, in order to prevent potential damage to ecosystems.